RELEVANSI PEMBACAAN DAN PENANDATANGANAN AKTA DI HADAPAN NOTARIS DALAM PEMBUATAN AKTA NOTARIL ERA DIGITAL - Endah Kusumaningrum (Faculty of Law, Tanjungpura University, 2023)
AbstractIn making a notary deed, the reading and signing of the deed is carried out in the physical presence of the appearers before the notary. Such provisions do not accommodate the demands of an all-digital era, while the authentic nature of the deed still needs to be maintained because it contains the hopes of the appearers for guaranteed certainty and legal protection of the rights of the appearers. This study aims to examine the relevance of applying the provisions of the physical presence of appearances before a Notary in reading and signing of deeds in making Notary deeds in the digital era and to examine the weaknesses of applying the reading and signing of deeds in making digital-based Notary deeds. The author uses normative legal research methods. The results show that the physical presence of appearers before a Notary at reading the deed in making a Notary deed is not fully relevant to be applied in the digital era because it does not accommodate the demands of the times that require practicality, but on the other hand the conventional way of signing the deed remains relevant to be implemented because it protects the authentic values ofthe Notary's deed. The weakness of digitizing the reading of the deed is that it allows a lack of correct understanding by the appearers of the contents of the deed so that it has the potential for conflict. Meanwhile, the digitization of the signing of the deed causes loss of jurisdiction, unfair competition among notaries, the uncertainty of the date of making the deed and the potential for cybercrime to occur.AbstrakDalam pembuatan akta Notaris, pembacaan dan penandatanganan akta dilakukan dengan kehadiran fisik para penghadap di hadapan Notaris. Ketentuan demikian tidak mengakomodir tuntutan zaman yang serba digital, sementara itu sifat otentik akta tetap perlu dijaga karena di dalamnya terdapat harapan parapenghadap akan jaminan kepastian dan perlindungan hukum atas hak para penghadap. Penelitian ini bertujuan untuk mengkaji relevansi penerapan ketentuan kehadiran fisik para penghadap di hadapan Notaris pada pembacaan dan penandatanganan akta dalam pembuatan akta Notaris di era digital danmengkaji kelemahan penerapan pembacaan dan penandatanganan akta pada pembuatan akta Notaris berbasis digital. Penulis menggunakan metode penelitian hukum normatif, Hasil penelitian menunjukkan bahwa kehadiran fisik para penghadap di hadapan Notaris pada pembacaan akta dalam pembuatan akta Notariil tidak sepenuhnya relevan untuk diterapkan di era digital karena tidak mengakomodir tuntutan zaman yang menghendaki kepraktisan, namun di sisi lain cara konvensional penandatanganan akta tetap relevan untuk diterapkan karena melindungi nilai-nilai otentik akta Notaris. Kelemahan digitalisasi pembacaan akta yaitu memungkinkan minimnya pemahaman yang benar oleh para penghadap terhadap isi akta sehingga berpotensi konflik. Sedangkan digitalisasi penandatangan akta menyebabkan hilangnya yurisdiksi kewenangan, persaingan tidak sehat diantara Notaris, tidak terjaminnya kepastian tanggalpembuatan akta serta berpotensi terjadi kejahatan siber.